Can Column Formaldehyde Observations Inform Air Quality Monitoring Strategies for Ozone and Related Photochemical Oxidants?. Issue 13 (27th June 2022) - Travis, K. R.; Judd, L. M.; Crawford, J. H.; Chen, Gao; Szykman, James; Whitehill, Andrew; Valin, Lukas C.; Spinei, Elena; Janz, Scott; Nowlan, Caroline R.; Kwon, Hyeong‐Ahn; Fried, Alan; et al.
Abstract: Formaldehyde column density (ΩHCHO) showed a potentially useful correlation with surface ozone during the LISTOS campaign on Long Island Sound and the KORUS‐AQ campaign in Seoul, South Korea. This builds on previous work that identified this relationship from in situ aircraft observations with similar findings for ground‐based and airborne remote sensing of ΩHCHO. In the Long Island Sound region, ΩHCHO and surface ozone exhibited strong temporal ( r 2 = 0.66) and spatial ( r 2 = 0.73) correlation. The temporal variability in ΩHCHO (∼1 Dobson units [DU]) was larger than the range in the spatial average (∼0.1 DU). The spatial average is most useful for informing ozone monitoring strategies, demonstrating the challenge in using ΩHCHO satellite data sets for this purpose. In Seoul, high levels of NO2 resulted in O x better correlating with ΩHCHO than surface ozone due to titration effects. The ΩHCHO–O x relationship may therefore reflect the sum of surface ozone and related photochemical oxidants, relevant to air quality standards set to regulate this quantity such as the U.S. EPA National Ambient Air Quality Standard (NAAQS). The relationship of ΩHCHO to O x shifted in Seoul during the campaign demonstrating the need to evaluate this relationship over longer time periods. With sufficient precision in future satellite retrievals, ΩHCHO observations could be useful for evaluating the adequacy of surface air quality monitoring strategies. Plain Language Summary: Surface ozone is hazardous to human health and the environment. Space‐based monitoring techniques provide the opportunity to improve our knowledge of regional surface ozone pollution. Ozone measurements from space have limited ability to detect surface concentrations. Observations of column formaldehyde, a trace gas produced during production of surface ozone, are correlated with surface ozone and related pollutants. This relationship points to a potential use of satellite observations for identifying regions of harmful ozone concentrations to complement sparse surface monitoring networks. Key Points: Column formaldehyde (ΩHCHO) is related spatially and temporally with surface ozone during the LISTOS and KORUS‐AQ field campaigns ΩHCHO better correlates with O x (≡ozone + NO2 ) which more broadly represents ozone and related photochemical oxidants Satellite ΩHCHO could be an indicator of ozone and related photochemical oxidants and inform air quality monitoring strategies